Analysis Of Antihypertensive Use In Pregnant Women With Severe Preeclampsia At Inpatient Ward of Dr.H. Abdoel Moeloek Hospital Bandar Lampung Period January-September 2016 - Rasmi Zakiah Oktarlina; Ety Apriliana; Tri Umiana Soleha; Reffilia Irfa (CV. Jasa Sukses Abadi, 2020)
Hypertension in pregnancy plays a major role in maternal and perinatal morbidity and mortality. Half to two-thirds of women with hypertension are diagnosed with preeclampsia and even eclampsia. One way to overcome hypertension is by antihypertensive pharmacological therapy. This study aims to analyze the use of antihypertensives in pregnant women with severe preeclampsia in the inpatient installation of RSUD Dr. H. Abdoel Moeloek for the period January-September 2016. Researchers used a cross-sectional approach and secondary data collection through 96 medical records of pregnant women with severe preeclampsia given antihypertensive drugs at RSUD Dr. H. Abdoel Moeloek during the period January-September 2016 based on dose accuracy, the accuracy of indication and accuracy of frequency is in accordance with the 2015 Queensland Health (Hypertensive Disorders of Pregnancy) and BNF (British National Formulary) 61 in 2011, with an exact indication of 83.3 %, the dose accuracy is 100%, and the frequency is 100%.